"Achieve the best while rushing against time": A grounded theory study on caring for low-income immigrant cancer patients at end of life. (February 2021) - Sacchi, Simona; Capone, Roberto; Ferrari, Francesca; Sforacchi, Federica; Di Leo, Silvia; Ghirotto, Luca
Background: Between 2000 and 2020, Europe experienced an annual net arrival of approximately 1.6 million immigrants per year. While having lower mortality rates, in the setting of severe diseases, immigrants bear a greater cancer-related burden due to linguistic and cultural barriers and socio-economic conditions. Professionals face a two-fold task: managing clinical conditions while considering the social, economic, cultural, and spiritual sphere of patients and their families. In this regard, little is known about the care provision to low-income immigrant cancer patients in real contexts. Aim: To investigate the perspective of professionals, family members, and stakeholders on the caring process of low-income immigrant cancer patients at the end of life. Design: A Constructivist Grounded Theory study. Setting/participants: The study, conducted at a Hospital in Northern Italy, involved 27 participants among health professionals, family caregivers, and other stakeholders who had recently accompanied immigrant cancer patients in their terminal phase of illness. Results: Findings evidenced that professionals feel they were not adequately trained to cope with immigrant cancer patients, nonetheless, they were highly committed in providing the best care they could, rushing against the (short) time the patients have left. Analyses evidenced four main categories: "providing and receiving hospitality, " "understanding each other, " "addressing diversity, " and "around the patient, " which we conceptualized under the core category "Achieve the best while rushing against time." Conclusions: The model reveals the activation of empathic and compassionate behavior by professionals. It evidences the need for empowering professionals with cultural competencies by employing interpreters and specific training programs.